AnalisisKemampuan Berpikir Kritis Siswa Dalam Menyelesaikan Soal Matematika - Selestina Nahak (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2022)
Abstract This study aims to determine the critical thinking ability of students of class XI IPA SMA Negeri Noemuti in solving math problems. The research method used is qualitative research methods. The subjects in this study were students of class XI IPA, totaling 20 students. The type of data collected is in the form of qualitative date, namely the results of the critical thinking ability test according to Perkins and Murphy including clarification, assessment, strategist/tactics, and inference. The results of data analysis obtained 60% of students included in the category of low critical thinking skills where students were only able to meet two critical thinking ability indicators with the ability to formulate then main points of the problem (clarification), giving the right reasons to produce the correct argument (assessment). 25% of students are included in the category of moderate critical thinking skills where students are able to meet three indicators with the ability to formulate the main points of the problem (clarification), give good reasons to produce correct arguments (assessment), solve problems with solutions based on concepts (strategist/tactics). 15% of students are included in the category of high critical thinking skills where students are able to meet four indicators with the ability to formulate the main points of the problem (clarification), provide good reasons to produce correct arguments (assessment), solve problems with solutions based on concepts (strategist/tactics), and draw sonclusions. Keyword: Analysis, critical thinking skills Abstrak Penelitian ini bertujuan untuk mengetahui kemampuan berpikir kritis siswa kelas XI IPA SMA Negeri Noemuti dalam menyelesaikan soal matematika. Metode penelitian yang digunakan yaitu metode penelitian kualitatif. Subjek dalam penelitian ini siswa kelas XI IPA yang berjumlah 20 orang siswa. Jenis data yang dikumpulkan berupa data kualitatif yaitu hasil tes kemampuan berpikir kritis dan hasil wawancara. Data dianalisis berdasarkan indikator berpikir kritis menurut Perkins & Murphy meliputiClarification, Assessment, Strategist/taktik, dan Inference. Hasil analisis datamenunjukkan 60% siswa termasuk dalam kategori kemampuan berpkir kritis rendah dimana siwa hanya mampu memenuhi dua indikator kemampuan berpikir kritis dengan kemampuan merumuskan pokok-pokok permasalahan (Clarification), memberikan alasan yang tepat untuk menghasilkan argumen yang benar (Assessment). 25% siswa termasuk dalam kategori kemampuan berpikir kritis sedang dimana siswa mampu memenuhi 3 indikator dengan kemampuan merumuskan pokok-pokok permasalahan (Clarification), memberikan alasan yang tepat untuk menghasilkan argumen yang benar (Assessment), menyelesaikan masalah dengan penyelesaian berdasarkan konsep (Strategist/taktik). 15% siswa termasuk dalam kategori kemampuan berpikir kritis tinggi dimana siswa mampu memenuhi 4 indikator dengan kemampuan merumuskan pokok-pokok permasalahan (Clarification), memberikan alasan yang tepat untuk menghasilkan argumen yang benar (Assessment), menyelesaikan masalah dengan penyelesaian berdasarkan konsep (Strategist/taktik), dan menarik kesimpulan (Inference). Kata Kunci: Analisis, Kemampuan berpikir kritis.